Analysis of Teacher Performance, Discipline, and Creativity on The Quality of Learning - Yudha, Rivo Panji; R, Tika Wijayanthi (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
This study aims to determine the influence of teachers' discipline, performance, and creativity on the quality of learning. The method used in this study was quantitative descriptive with 50 respondents and data analysis used, namely Partial Least Square (SmartPLS 4.0). The research findings show that(1) The results of this study found that discipline positively and significantly affected performance(2) The results of this study found that discipline positively had no effect and was not significant on creativity. (3) The results of this study found that discipline positively had no effect and was not significant on the quality of learning. (4) The results of this study found that performance positively had no effect and was not significant on creativity. (5) The results of this study found that performance positively had no effect and was not significant on the quality of learning. . (6) The results of this study found that creativity positively and significantly affects the quality of learning.